Genomic analysis of Salmonella enterica serotype Paratyphi A during an outbreak in Cambodia, 2013–2015. Issue 11 (30th November 2016) - Kuijpers, Laura Maria Francisca; Le Hello, Simon; Fawal, Nizar; Fabre, Laetitia; Tourdjman, Mathieu; Dufour, Muriel; Sar, Dara; Kham, Chun; Phe, Thong; Vlieghe, Erika; Bouchier, Christiane; Jacobs, Jan; et al.
Abstract : In 2013, an unusual increase in the number of Salmonella enterica serotype Paratyphi A ( Salmonella Paratyphi A) infections was reported in patients in Phnom Penh, Cambodia, and in European, American and Japanese travellers returning from Cambodia. Epidemiological investigations did not identify a common source of exposure. To analyse the population structure and genetic diversity of these Salmonella Paratyphi A isolates, we used whole-genome sequencing on 65 isolates collected from 1999 to 2014: 55 from infections acquired in Cambodia and 10 from infections acquired in other countries in Asia, Africa and Europe. Short-read sequences from 80 published genomes from around the world and from 13 published genomes associated with an outbreak in China were also included. Pulsed-field gel electrophoresis (PFGE) was performed on a subset of isolates. Genomic analyses were found to provide much more accurate information for tracking the individual strains than PFGE. All but 2 of the 36 isolates acquired in Cambodia during 2013–2014 belonged to the same clade, C5, of lineage C. This clade has been isolated in Cambodia since at least 1999. The Chinese outbreak isolates belonged to a different clade (C4) and were resistant to nalidixic acid, whereas the Cambodian outbreak isolates displayed pan-susceptibility to antibiotics. Since 2014, the total number of cases has decreased, but there has been an increase in the frequency with which nalidixic acid-resistant C5 isolates are isolated. The frequency of these isolates should be monitored over time, because they display decreased susceptibility to ciprofloxacin, the first-choice antibiotic for treating paratyphoid fever.